Seasonal Dynamics and Ecological Significance of Bird Diversity in Tipeshwar Wildlife Sanctuary, Maharashtra, India - Ramzan S. Virani (Journal of Advanced Zoology, 2021)
This study aimed to assess the bird richness and abundance in the Tipeshwar Wildlife Sanctuary, located in the Yavatmal district of Maharashtra, India. The comprehensive survey identified a total of 256 bird species within the sanctuary, shedding light on the dynamic patterns of bird abundance across various seasons. The findings indicate an increase in bird population during the monsoon and winter months, contrasting with a decline observed in the summer and pre-monsoon periods. These results contribute to the understanding of the avian community within the Tipeshwar Wildlife Sanctuary, emphasizing its role as a habitat with a healthy environmental setup conducive to supporting diverse bird populations. The variations in bird abundance throughout the seasons underscore the dynamic nature of avian communities within this ecosystem.